Answer:
The first one!
Step-by-step explanation:
Answer:
A correctly displays the number.
Step-by-step explanation:
B. (7, 15, 17)
C. (9, 12, 16)
D. (7, 24, 25)
The set of side lengths (7, 15, 17) represents a right angled triangle
For the given set of side lengths to represent a right angled triangle, the
Pythagoras relation should be satisfied by the side lengths of the triangle.
We can write the given relation as -
h² = b² + p²
Consider the side length pairs as -
(7, 15, 17)
We can arrange the sides as -
17² = 15² + 7²
289 = 225 + 49
289 = 289
The set of side lengths (7, 15, 17) represents a right angled triangle.
To solve more questions on triangles, visit the link-
#SPJ2
Answer:
Step-by-step explanation:
B
Write the equation y - 3 = 4(x + 1) in standard form.
Write the equation y + 7 = -2(x - 3) in slope-intercept form.
The equation y - 5 = 3(x - 2)
is written in point-slope form. Write this equation in the
following ways:
a. slope-intercept form
b. standard form
So remember that slope-intercept form is y = mx+b (m = slope, b = y-intercept) and standard form is ax+by = c. (a and b are coefficients and c is the constant)
Starting with the first question: 9x + 2y = 6
Firstly, subtract 9x on both sides: 2y = -9x + 6
Next, divide both sides by 2, and your equation will be y = -4.5x + 3
Now with the next equation: y - 3 = 4(x + 1)
Firstly, foil 4(x + 1): y - 3 = 4x + 4
Next, subtract y on both sides: -3 = 4x - y + 4
Next, subtract 4 on both sides, and your answer will be: -7 = 4x - y
Next equation: y + 7 = -2(x - 3)
Firstly, foil -2(x - 3): y + 7 = -2x + 6
Next, subtract 7 on both sides of the equation, and your answer will be: y = -2x - 1
Next: y - 5 = 3(x - 2) (part a)
Firstly, foil 3(x - 2): y - 5 = 3x - 6
Next, add 5 on both sides, and your equation is: y = 3x - 1
Next, y - 5 = 3(x - 2) (part b)
Firstly, foil 3(x - 2): y - 5 = 3x - 6
Next, subtract y on both sides of the equations: -5 = 3x - y - 6
Next, add 6 on both sides of the equation, and your answer will be: 1 = 3x - y
x= -4 y=16-5=11
x= -2 y=4-5= -1
x= -1 y=1-5= -4
x= 0 y= -5
x= 1 y= 1-5= -4
x= 2 y=4-5= -1
x=3 y=9-5=4
x=4 y=16-5=11
Teaspoons of honey 1 2 4 7
Total calories 504 568 696 888
A teaspoon of sugar has____ calories.
A teaspoon of honey has____ calories
2. 2 open parentheses x plus 10 close parentheses over x minus 9
3. quantity 2 x plus 5 over x minus 9
4. quantity 13 x plus 5 over 5 x minus 9
Answer:
Step-by-step explanation:
Quantity 2 x squared plus 13 x plus 20 all over x squared minus 5 x minus 36
Correct option is option 3